Meningkatkan Prestasi Belajar melalui Model Pembelajaran Cooperative Learning Strategies (CLS) - Nur Widhihastuti; Supardi Supardi (PANDITA : Interdisciplinary Journal of Public Affairs, 2023)
The selection of the right learning model greatly affects the success in determining the high and low results achieved by students in carrying out learning. However, to be able to have the right learning model, careful observation is needed by looking for the causes behind the difficulty of students learning the given material. The emphasis is on the importance of activities and interactions during the learning process to achieve what is the purpose of teaching. Thus the success of students in the learning process will achieve maximum results. Improve student learning outcomes with the Cooperative Learning Strategy learning model in the process of implementing Biology subject learning in class XII Science 2 at SMA Negeri 2 Cikarang Utara. This model is considered appropriate to be applied to students because it has the principle of responsibility between individuals, interdependence in positive terms, communicative among others, students, doing face-to-face to interact, accustomed to evaluating in carrying out a better process. Achievement in carrying out the learning process using this model gets significant results in improving student learning outcomes. The basis for this achievement is accompanied by data during the model implementation process